2019
DOI: 10.1111/jocs.14284
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the recently noted surgical outcome of isolated total anomalous pulmonary venous connection repair: A single‐secondary center experience

Abstract: Background and Aim of the Study: Total anomalous pulmonary venous connection (TAPVC) is a rare cyanotic congenital heart defect. This study aimed to evaluate the outcome of isolated TAPVC repairs and the prognoses of affected patients in the last 12 years at a single center. Methods: We retrospectively analyzed the medical records of 51 patients who underwent isolated TAPVC repair from 2007 to 2018. Results: The median age at operation was 19 days, and the median body weight was 3.3 kg. Thirteen (25.5%) patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
7
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 27 publications
(85 reference statements)
0
7
0
Order By: Relevance
“…These techniques are associated with some inherent complications, such as the need for reintervention (due to occlusion of the stent or the recurrence of PVO) and the need for anticoagulation. Research has shown that the mortality rate is 38% at 1 year and that the reintervention rate is 58% at 1 year [ 2 , 5 , 19 ]. Moreover, not all patients could tolerate these palliative measures, and patients needed to undergo surgery to correct the anomalous pulmonary veins [ 5 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These techniques are associated with some inherent complications, such as the need for reintervention (due to occlusion of the stent or the recurrence of PVO) and the need for anticoagulation. Research has shown that the mortality rate is 38% at 1 year and that the reintervention rate is 58% at 1 year [ 2 , 5 , 19 ]. Moreover, not all patients could tolerate these palliative measures, and patients needed to undergo surgery to correct the anomalous pulmonary veins [ 5 ].…”
Section: Discussionmentioning
confidence: 99%
“…The outcomes of the surgical repair of a total anomalous pulmonary venous connection (TAPVC) have historically improved, with the mortality rates reported in the literature ranging from 10 to 20% [ 1 , 2 ] or even below 7% [ 3 , 4 ], while emergency surgery reported had mortality rates as high as 25% [ 1 , 2 ].some patients have a risk of progressive pulmonary hypertension (PH) due to pulmonary venous obstruction (PVO), and other patients present with increasing cyanosis, tachypnea, hepatomegaly, hypoxia, gasping, or poor feeding [ 5 ] due to a delayed diagnosis. All these patients have a risk of progressive PH, suffer from severe respiratory distress and metabolic acidosis and require immediate intubation and inotropic support; more importantly, an emergency operation is needed.…”
Section: Introductionmentioning
confidence: 99%
“…Research has shown that the mortality rate is 38% at 1 year and that the reintervention rate is 58% at 1 year 2,5,19 . Moreover, not all patients could tolerate these palliative measures, and patients needed to undergo surgery to correct the anomalous pulmonary veins 5 .…”
Section: Discussionmentioning
confidence: 99%
“…The outcomes of the surgical repair of a total anomalous pulmonary venous connection (TAPVC) have historically improved, with the mortality rates reported in the literature ranging from 10-20% 1,2 or being below 7% 3,4 . In contrast, some patients have a risk of progressive pulmonary hypertension (PH) due to pulmonary venous obstruction (PVO), and other patients present with increasing cyanosis, tachypnea, hepatomegaly, hypoxia, gasping, or poor feeding 5 due to a delayed diagnosis.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation